Cloning and Developmental Expression of Methoprene-tolerant (Met) in Diapausing Larvae of the Bamboo Borer, Omphisa fuscidentalis Hampson - ,Suphawan Suang (Science Faculty of Chiang Mai University, 2019)
In insects, juvenile hormone (JH) and 20-hydroxyecdysone (20E) regulate larval growth and molting. Decline in JH and increment in ecdysteroid titer lead to termination of larval diapause in lepidopteran insects, while high levels of JH in the hemolymph allow the larva stage to be maintained. However, little is known about how JH regulates larval diapause in the bamboo borer, Omphisa fuscidentalis. One of the main players in hormonal signaling for JH is methoprene-tolerant (Met), which plays the role as a candidate of JH receptor. We assumed that the Met expression undergoes change during the larval diapause stage. Therefore, we cloned and sequenced the O. fuscidentalis methoprene-tolerant (OfMet) in this study. The partial sequence of the OfMet cDNA encodes 248 amino acids. The OfMet is highly similar (63.4%) to the silkworm (Bombyx mori) Met. The quantitative real-time polymerase chain reaction (qRT-PCR) reveals that the OfMet mRNA was expressed in subesophageal ganglion (SG), prothoracic gland (PG), thoracic ganglia (TG), abdominal ganglia (AG), Malpighian tubules (MT), fat body (Ft) and integument (Inm). In addition, the expression level of the OfMet mRNA in the SG was consistently high during the fifth larval instar, and increased moderately in early diapause. The expression was high in mid-diapause, and decreased in late diapause until the pupal stage. These results given here are the first evidence to demonstrate the developmental expression profile of the OfMet in the diapausing larvae of this insect.